The Greengrocer's Kin. Issue 2 (May 2018) - Williams, Kieran
The writings of Václav Havel are haunted by the character of the seemingly powerless man who nevertheless shares responsibility for the perpetuation of an unjust system. He is the incarnation of what Havel in The Power of the Powerless called the "instrument of a mutual totality, the auto-totality of society" that does much of the policing work of the post-totalitarian state. The greengrocer of that essay's third section was not the only such embodiment; he had contemporaries in the characters of the famous Vaněk plays. But the cast is not limited to them either; we can find examples of this phenomenon in some of Havel's earliest essays, and in some of his less known later plays that explore the social dynamics that underpin and undermine political systems.